Currículo cultural: brincadeiras, jogos e lutas de matrizes indígenas e africanas na Educação Física escolar - Rosa, Alisson Aurélio (Universidade Federal de São Carlos, 2023)
The Brazilian society features influences marked by African and indigenous cultures, however, when we step into the schools and analyze the pedagogical practices of most of the teachers, it is possible to verify the near non-existence of these cultural manifestations, demanding changes in the mentality of the whole school community. Thus, it is necessary to accept the challenge of an education based on the perspective of these ethnic groups. The present work analyzed a teaching proposal that thematizes African and indigenous body practices in elementary school Physical Education classes. Supported by the conception of cultural curriculum, this research aims to lead students and teacher-researcher to understand how the thematization of such body practices can be important for the decolonization of the curriculum. The research was carried out qualitatively, during one semester, with 5th grade students of a public school in the city of Araraquara/SP, in which the teacher-researcher used class diaries as a tool for data collection, with the intention of recording the information collected during the investigative process, in the light of the didactic procedures and pedagogical principles of the cultural curriculum. Moreover, the present work used action research, valuing the participation of the subjects and the construction of democratic relations. For the analysis and interpretation of the collected data, four categories were established, as follows: 1. evaluation under the aegis of cultural analysis, which privileged the dialog among the subjects in a deep analysis of the social occurrence of the body manifestations; 2. recognition of the students' knowledge, which, by mapping the body practices of groups that are often silenced, made it possible to theme indigenous and African practices; 3. Livings, dialogues, and re-significations, in which, far from resorting to rationalized practices, the students elaborated other ways to experience the manifestations that are the theme of the study and, 4. Expansion and deepening of knowledge, in which, through problematization, it aimed to counteract the discourses rooted in racist representations about the indigenous and the black. The expectation of the study was to provide educational spaces that would enable the combat against coloniality, privileging black and indigenous manifestations and, in this way, we consider that we can contribute to a change in the educators' mentality when they become convinced of the search for new paths regarding their teaching activities. The advent of more equitable and fairer educational practices may contribute to the implementation of Laws 10.639/03 and 11.645/08, besides promoting curricular justice through the balanced selection of study themes and the decolonization of the curriculum through themes related to the subordinate body culture. Having that in mind, the conclusion is that we are only making the curricular justice if we recognize the cultural heterogeneity, demanding from the educators that they establish other visions about the indigenous and African cultural manifestations
Cultural curriculum: plays, games and struggles of indigenous and african headquarters in school Physical Education
Keywords: Educação física escolar; Currículo cultural; Práticas corporais africanas e indígenas; School physical education; Cultural curriculum; African and indigenous body practices; CIENCIAS DA SAUDE::EDUCACAO FISICA